A carbon-based catalyst and its preparation method and application

By modifying coal-based activated carbon to prepare carbon-based catalysts, combined with ex situ catalytic pyrolysis and optimized process conditions, the problems of poor selectivity and stability of existing catalysts were solved, and efficient preparation of liquid fuels that meet aviation fuel standards was achieved, which has significant industrial application value.

CN120094569BActive Publication Date: 2025-10-03HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510251996.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-10-03
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

Existing catalysts have problems such as poor selectivity and stability, high cost, and complex preparation in the pyrolysis process of waste plastics, making it difficult to effectively improve the output and quality of liquid fuel.

Method used

A carbon-based catalyst is prepared by modifying coal-based activated carbon with hydrogen peroxide. By controlling the impregnation time, concentration and drying temperature, activated carbon with mainly macropores is formed. It is used in the ex situ catalytic pyrolysis process. By controlling the pyrolysis and catalytic temperatures and the inert gas flow rate, the condensation conditions are optimized and highly selective liquid fuel is prepared.

Benefits of technology

A highly selective and stable carbon-based catalyst has been achieved, with a liquid fuel selectivity of no less than 93%, which meets aviation fuel standards. The process is simple, environmentally friendly and pollution-free, improving industrial production efficiency and fuel quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120094569B_ABST
    Figure CN120094569B_ABST
Patent Text Reader

Abstract

The present invention relates to a carbon-based catalyst, a preparation method, and an application thereof. The preparation method comprises the following steps: washing coal-based activated carbon with deionized water for use, pouring hydrogen peroxide with a mass concentration of 10% to 20% into the coal-based activated carbon, sealing and impregnating the carbon, washing the impregnated coal-based activated carbon with deionized water, and drying the carbon-based catalyst. The inventive method is simple, low-cost, and green and pollution-free. The prepared catalyst has good selectivity for aviation fuel, a high conversion rate, is not easily deactivated, and can be widely applied to existing oil refining and chemical equipment and production processes. The prepared aviation fuel has an excellent component ratio and high quality. In addition, waste plastics can be efficiently converted into gasoline or diesel simply by changing the catalytic temperature, which has the significant advantage of controllable target products, thereby greatly improving industrial production efficiency. The invention can effectively achieve high-value reuse of solid waste resources, alleviate their environmental pollution problems, and has good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a carbon-based catalyst and a preparation method and application thereof. Background Art

[0002] Through catalytic pyrolysis technology, waste plastics can be converted into energy products such as high-value transportation fuels, which can achieve efficient recycling and reuse of waste plastics and solve the problem of plastic pollution.

[0003] Catalysts are the key to improving reaction efficiency and optimizing product distribution during catalytic pyrolysis reactions. Commonly used catalysts include molecular sieves, bifunctional metals, and activated carbons. Molecular sieve catalysts have the advantages of high specific surface area and porosity. Currently, in the available literature, the highest aviation fuel yield obtained using molecular sieve catalysts is 80.8wt.% (Energy Conversion and Management 299(2024), 117825), but the selectivity is only 73.1%, and the catalyst has poor stability and is easily deactivated. Bifunctional metal catalysts have the advantages of good stability, strong activity, and high selectivity. Currently, in the available literature, the highest aviation fuel selectivity obtained using bifunctional metal catalysts is 80.27% (FuelProcessing Technology 230(2022), 107205), but the liquid oil yield is only 48.71%, and the proportion of aromatics reaches 53.46%, which does not meet the aviation fuel standards. It also has the disadvantages of high cost and complex preparation methods.

[0004] Activated carbon catalysts have become a research hotspot in recent years due to their unique advantages such as low cost and long catalyst life. Currently, in the available literature, the selectivity of liquid aviation fuel prepared from biomass-based activated carbon can reach up to 93.13% (Industrial & Engineering Chemistry Research 59.39(2020):17451-17461), but alkanes only account for 39.11% of it, and the quality is far below the aviation fuel standard; therefore, there is an urgent need to develop new and efficient catalyst preparation methods and apply them to the field of waste plastic pyrolysis to improve the yield and quality of liquid fuel, and at the same time promote the commercialization of plastic waste resource utilization. Summary of the Invention

[0005] The purpose of the present invention is to provide a carbon-based catalyst and its preparation method and application in order to solve the above problems.

[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0007] The present invention provides a method for preparing a carbon-based catalyst. Coal-based activated carbon is washed with deionized water and then set aside. Hydrogen peroxide with a mass concentration of 10% to 20% is poured into the coal-based activated carbon to seal and impregnate it. The impregnated coal-based activated carbon is washed with deionized water and then dried to obtain the carbon-based catalyst.

[0008] As a further optimization scheme of the present invention, the particle size of the coal-based activated carbon is 420 to 590 μm; the amount of hydrogen peroxide with a mass concentration of 10% to 20% used to impregnate the coal-based activated carbon is 30 mL / g; the impregnation time is 24 hours; treatment with hydrogen peroxide of different concentrations has a significant effect on the structure of the coal-based activated carbon, namely, at low concentrations, the coal-based activated carbon produces new small pores to increase the attachment rate of active groups, and at higher concentrations, hydrogen peroxide corrodes the small pores by oxidizing the surface of the carbon material, forming activated carbon with mainly large pores and richer active groups; by controlling the impregnation ratio and time, the coal-based activated carbon can be fully and evenly oxidized and modified by hydrogen peroxide;

[0009] The drying temperature is 105°C and the drying time is 24h. By controlling the drying temperature and time, it is ensured that all moisture in the modified activated carbon is removed.

[0010] The present invention also provides a carbon-based catalyst prepared by the above-mentioned method for preparing a carbon-based catalyst.

[0011] The present invention also provides an application of the carbon-based catalyst in preparing liquid fuel by catalytic pyrolysis of plastics.

[0012] As a further optimization scheme of the present invention, the plastic is at least one of low-density polyethylene (LDPE), high-density polyethylene (HDPE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyethylene terephthalate (PET); the liquid fuel includes gasoline C5~C12, aviation fuel C8~C16, and diesel C10~C23.

[0013] As a further optimized solution of the present invention, the liquid fuel is aviation fuel C8-C16.

[0014] The present invention also provides a method for preparing liquid fuel by catalytic pyrolysis of plastic using the above-mentioned carbon-based catalyst, comprising the following steps:

[0015] (1) using an ex situ catalytic pyrolysis method to pyrolyze the plastic, and using an inert gas as a carrier gas to carry the plastic pyrolysis gas into a reactor equipped with the carbon-based catalyst for a catalytic pyrolysis reaction to obtain a gaseous pyrolysis product;

[0016] (2) The gaseous pyrolysis products are passed through a condensation device containing dichloromethane and methanol, condensed, and collected to obtain liquid fuel.

[0017] It should be noted that although plastics can be cracked into gaseous products in a short period of time by rapid heating, the two processes of thermal cracking and catalytic reaction can be separated by heterogeneous catalytic pyrolysis, which facilitates catalyst activation and catalytic temperature control, thereby improving the selectivity of liquid products (such as diesel, aviation fuel, and gasoline).

[0018] As a further optimization solution of the present invention, the plastic is at least one of low-density polyethylene (LDPE), high-density polyethylene (HDPE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), and polyethylene terephthalate (PET);

[0019] The particle size of the plastic is 1 to 100 mm;

[0020] The mass ratio of the plastic to the carbon-based catalyst is 1:2 to 2:1.

[0021] As the mass of plastic raw materials increases, the oil yield gradually increases, but the quality of the oil product will decrease; when the raw materials increase to a certain mass, wax will be produced; therefore, the mass ratio of plastic to catalyst can be adjusted within the above range to improve the quality of the liquid oil.

[0022] As a further optimization scheme of the present invention, in step (1), the pyrolysis temperature is 450°C to 600°C; the pyrolysis reaction time is 25 minutes;

[0023] Different temperatures have a significant impact on product formation. At lower temperatures, liquid products (such as oils) and solid products (such as waxes) are more likely to form. At lower temperatures, polymer chains break to form larger hydrocarbons, while at higher temperatures, gaseous products such as H2, CH4, and C2H2 are more likely to form. The pyrolysis temperature and time can be controlled within the above range to obtain pyrolysis products that are beneficial to subsequent reactions.

[0024] In step (1), the inert gas is nitrogen, and the flow rate of the nitrogen is 55 to 85 mL / min;

[0025] Different flow rates also have a significant impact on product distribution. At higher flow rates, plastic pyrolysis products quickly pass through the catalyst, forming medium- and long-chain hydrocarbons, thereby improving the selectivity of diesel and aviation fuel. At lower flow rates, aromatics and short-chain alkanes are more likely to form, thereby improving the selectivity of gasoline. The inert gas flow rate can be controlled within the above range to obtain highly selective liquid aviation fuel.

[0026] In step (1), the catalytic temperature is 450°C to 600°C, and the catalytic reaction time is 25 minutes;

[0027] Catalytic temperature primarily influences product distribution and selectivity. The products from the first stage of pyrolysis undergo further cracking and reforming under the action of the catalyst. At lower catalytic temperatures, the products tend to form long-chain alkanes, thereby improving selectivity for diesel and aviation fuel. At higher catalytic temperatures, the products tend to form low-quality hydrocarbons, thereby improving selectivity for gasoline. Controlling the catalytic temperature and time within this range effectively yields highly selective liquid fuels.

[0028] As a further optimized solution of the present invention, in step (2), the condensation temperature is -15°C to 0°C, and the volume ratio of dichloromethane to methanol is 1:1.

[0029] The beneficial effects of the present invention are:

[0030] 1) The present invention uses hydrogen peroxide as an activating agent and coal-based activated carbon as a modified material to prepare a coal-based activated carbon catalyst by an impregnation method. The entire process is simple, non-toxic, harmless, green and pollution-free, with low raw material cost, and has high industrial application value;

[0031] 2) The carbon-based catalyst prepared by the present invention has good selectivity for aviation fuel C8-C16, high conversion rate, high activity, excellent stability, and is not easily deactivated. The aviation fuel prepared has an excellent component ratio and high quality, and can be widely used in existing refining and chemical equipment and production processes;

[0032] 3) The carbon-based catalyst prepared by the present invention can also efficiently convert waste plastics into gasoline C5-C12 or diesel C10-C23 simply by changing the catalytic temperature, which has the significant advantage of controllable target products, thereby significantly improving industrial production efficiency;

[0033] 4) In the aviation fuel prepared by the present invention, the selectivity of aviation fuel C8-C16 in the liquid product is not less than 93%, of which the mass proportions of alkanes and aromatics are 78.36% and 20.93%, respectively, meeting the component ratio standards for aviation fuel. At the same time, the mass ratio of the liquid product in the total gas-liquid-solid product is not less than 90%, demonstrating a higher liquid yield and better quality.

[0034] 5) The present invention uses waste plastic as raw material to prepare liquid fuel. This technology not only alleviates the problem of increasing shortage of fossil fuels, but also reduces environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a flow chart of preparing a carbon-based catalyst and using the carbon-based catalyst to catalyze and pyrolyze plastic to prepare liquid fuel.

[0036] Figure 2This is an experimental diagram showing the effects of different mass ratios of the carbon-based catalyst and raw material (plastic) of the present invention on the selectivity of aviation fuel.

[0037] Figure 3 This is an experimental diagram showing the effects of different mass ratios of the carbon-based catalyst and raw materials of the present invention on the selectivity of various components in aviation fuel.

[0038] Figure 4 This is an experimental diagram showing the effects of the carbon-based catalyst and raw materials of the present invention on the selectivity of aviation fuel and the selectivity of each component in aviation fuel through catalytic reactions at different catalytic temperatures.

[0039] Figure 5 This is an experimental diagram showing the effects of the carbon-based catalyst and raw materials of the present invention on the selectivity of different liquid fuels under catalytic reactions at different catalytic temperatures.

[0040] Figure 6 This is an experimental diagram showing the effect of the carbon-based catalyst of the present invention on the selectivity of various components in aviation fuel after continuous recycling for 1-10 times. DETAILED DESCRIPTION

[0041] The present application is described in further detail below in conjunction with the accompanying drawings. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0042] 1. Materials

[0043] 1. Plastics: low-density polyethylene (LDPE), high-density polyethylene (HDPE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyethylene terephthalate (PET). The following tests use low-density polyethylene (LDPE) with a particle size of 1 to 100 mm.

[0044] 2. Coal-based activated carbon: particle size is 420-590μm.

[0045] Unless otherwise specified, the methods used in this application are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.

[0046] 2. Methods

[0047] 2.1. Method for preparing liquid fuel by catalytic pyrolysis of plastic using carbon-based catalyst (e.g. Figure 1 ), the steps are as follows:

[0048] (1) Preparation of carbon-based catalyst: Weigh 1g of coal-based activated carbon and place it in a container. Pour 30mL of 0% to 20% hydrogen peroxide into the container, seal the container and let it stand at room temperature for 24 hours. Then, pour out the excess liquid and wash it with deionized water 2 to 3 times. Place it in a constant temperature drying oven at 105°C and dry it for 24 hours to obtain (0% to 20%) O-AC catalyst for use.

[0049] (2) Place 100 mg of LDPE pellets in a pyrolysis system, set the pyrolysis temperature to 450°C to 600°C, the pyrolysis time to 25 min, and use nitrogen as the carrier gas at a nitrogen flow rate of 55 to 85 mL / min;

[0050] (3) Weigh a carbon-based catalyst with a mass ratio of 1:1 to plastic and place it in the catalytic system. Set the temperature of the catalytic section to 450°C to 600°C. Activate for 20 minutes to remove impurities such as moisture and stabilize its performance. Open the high-temperature valve and raise the pyrolysis furnace. Nitrogen carries the pyrolysis product formed in step (2) into the catalytic section. React for 25 minutes to obtain a mixed product.

[0051] (4) The mixed product obtained in step (3) is passed through a three-stage cold trap filled with dichloromethane and methanol (v / v=1). The temperature of the cold trap is -15°C to 0°C (-15°C is used in the experiment of the present invention). The condensable components are condensed and collected as pyrolysis oil, and the non-condensable components are combustible gases (H2 and CH4, etc.), which can subsequently be used to circulate heat for the pyrolysis system.

[0052] 2.2 Single-factor experiment

[0053] 2.2.1. Based on the method in step 2.1, the effect of pyrolysis temperature on liquid fuel selectivity was tested. The adjustment of pyrolysis temperature and the control of other factors are shown in Table 1:

[0054] Table 1 Single factor experimental conditions (pyrolysis temperature)

[0055]

[0056] The liquid fuels prepared in the above test groups 1-4 were subjected to GC-MS testing. The product distribution results of the liquid fuels are shown in Table 2:

[0057] Table 2 Product distribution statistics of liquid fuels in test groups 1-4

[0058]

[0059] Note: Oil yield = oil mass / plastic mass * 100%; gasoline range yield = gasoline mass / oil mass * 100%; aviation fuel range yield = aviation fuel mass / oil mass * 100%; diesel range yield = diesel mass / oil mass * 100%.

[0060] Experimental conclusion: From the data of the above test groups 1 to 4, it can be seen that when the mass ratio of plastic to catalyst is fixed at 1:1, the catalytic temperature (500℃) and nitrogen flow rate (65mL / min) remain unchanged. By changing the thermal cracking temperature (450-600℃), significant differences in oil yield can be observed; too low a thermal cracking temperature will lead to insufficient pyrolysis of LDPE, while too high a pyrolysis temperature will increase the production of gas and coke. Therefore, the liquid oil yield first increases and then decreases with the increase of pyrolysis temperature.

[0061] 2.2.2. Based on the method in step 2.1 and test group 1, the nitrogen flow rate was adjusted and the effect of the nitrogen flow rate on the liquid fuel selectivity was tested. The adjustment of the thermal cracking temperature and the control of other factors are shown in Table 3:

[0062] Table 3 Single factor experimental conditions (nitrogen flow rate)

[0063]

[0064] The liquid fuels prepared in the above test groups 1, 5-7 were subjected to GC-MS analysis. The product distribution results of the liquid fuels are shown in Table 4:

[0065] Table 4 Product distribution statistics of liquid fuels in test groups 1, 5-7

[0066]

[0067] Note: Oil yield = oil mass / plastic mass * 100%; gasoline range yield = gasoline mass / oil mass * 100%; aviation fuel range yield = aviation fuel mass / oil mass * 100%; diesel range yield = diesel mass / oil mass * 100%.

[0068] Experimental conclusion: From the data of the above test groups 1, 5 to 7, it can be concluded that when the ratio of raw material to catalyst is fixed at 1:1, the pyrolysis temperature and catalytic temperature are kept unchanged at 500°C, and only the nitrogen flow rate is changed (range: 55-85 mL / min), significant differences can be observed in the oil yield and the selectivity for gasoline, aviation fuel and diesel; with the increase of nitrogen flow rate, the residence time of plastic pyrolysis gas on the catalyst is shortened, resulting in insufficient contact between the pyrolysis gas and the catalyst. This phenomenon weakens the catalyst's ability to break CC bonds and CH bonds, and tends to form alkanes larger than C16. Therefore, the selectivity for gasoline and aviation fuel decreases, while the selectivity for diesel gradually increases.

[0069] 2.2.3. Based on the method in step 2.1 and test group 1, only the mass ratio of plastic to catalyst was adjusted, and the effect of the mass ratio of plastic to catalyst on the selectivity of liquid fuel and the selectivity of each component in aviation fuel was tested. The adjustment of thermal cracking temperature and the control of other factors are shown in Table 5:

[0070] Table 5 Single factor experimental conditions (mass ratio of plastic to catalyst)

[0071]

[0072]

[0073] The liquid fuel prepared in the above test groups 1, 8, and 9 was subjected to GC-MS testing. The product distribution results of the liquid fuel are as follows: Figure 2-3 As shown in Table 6:

[0074] Table 6 Product distribution statistics of liquid fuel in test groups 1, 8, and 9

[0075]

[0076] Note: Oil yield = oil mass / plastic mass * 100%; gasoline range yield = gasoline mass / oil mass * 100%; aviation fuel range yield = aviation fuel mass / oil mass * 100%; diesel range yield = diesel mass / oil mass * 100%.

[0077] Experimental conclusion: Based on the data of the above test groups 1, 8, and 9 and Figure 2-3 It can be concluded that under the same conditions of pyrolysis temperature (500℃), catalytic temperature (500℃) and nitrogen flow rate (65mL / min), as the mass ratio of plastic to catalyst (15% O-AC) increases from 1:2 to 2:1, the oil yield gradually increases; however, due to the limited active sites of the catalyst, when the ratio continues to increase, the catalytic effect gradually decreases, resulting in an increase in long-chain alkanes greater than C16 in the product; the selectivity of aviation fuel and gasoline decreases, while the selectivity of diesel increases.

[0078] 2.2.4. Based on the method in step 2.1 and test group 1, only the hydrogen peroxide concentration was adjusted, and the effect of hydrogen peroxide concentration on liquid fuel selectivity was tested. The adjustment of thermal cracking temperature and the control of other factors are shown in Table 7:

[0079] Table 7 Single factor experimental conditions (hydrogen peroxide concentration)

[0080]

[0081] Note: “-” indicates that coal-based activated carbon that has not been modified with hydrogen peroxide is used as the catalyst, that is, commercially available coal-based activated carbon.

[0082] The liquid fuels prepared in the above test groups 1, 5-7 were subjected to GC-MS analysis. The product distribution results of the liquid fuels are shown in Table 8:

[0083] Table 8 Product distribution statistics of test groups 1 and 10-12 liquid fuel

[0084]

[0085] Note: Oil yield = oil mass / plastic mass * 100%; gasoline range yield = gasoline mass / oil mass * 100%; aviation fuel range yield = aviation fuel mass / oil mass * 100%; diesel range yield = diesel mass / oil mass * 100%.

[0086] Experimental conclusion: From the data of the above test groups 1, 10-12, it can be concluded that when the ratio of raw material to catalyst is fixed at 1:1, under the same conditions of pyrolysis temperature (500℃), catalytic temperature (500℃) and nitrogen flow rate (65mL / min), as the concentration of hydrogen peroxide increases, the selectivity of gasoline and aviation fuel gradually increases, while the selectivity of diesel decreases; this is because hydrogen peroxide treatment can increase the pores of activated carbon and increase the content of weakly acidic groups, thereby promoting the breakage of CC bonds and CH bonds, and converting long-chain molecules in the pyrolysis gas into short-chain alkanes and aromatics; however, if the acidity is too strong or the pores are too small, the small molecule chains will be further broken to generate gaseous products such as H2 and CH4, so the liquid oil yield shows a trend of first increasing and then decreasing;

[0087] Compared with unmodified commercially available coal-based activated carbon, the coal-based activated carbon catalyst modified with 15% hydrogen peroxide showed significant advantages in the catalytic oil production process of plastic pyrolysis gas: the oil yield was as high as 90.9%, and no wax was generated; the aviation fuel selectivity was increased by 10.51%.

[0088] 2.2.5. Based on the method in step 2.1 and test group 1, only the catalytic reaction temperature was adjusted, and the effect of the catalytic reaction temperature on the selectivity of liquid fuel and the selectivity of each component in aviation fuel was tested. The adjustment of the thermal cracking temperature and the control of other factors are shown in Table 9:

[0089] Table 9 Single factor experimental conditions (catalytic reaction temperature)

[0090]

[0091] The liquid fuel prepared in the above test groups 1, 13-15 was subjected to GC-MS testing. The product distribution results of the liquid fuel were as follows: Figure 4-5 As shown in Table 10:

[0092] Table 10 Product distribution statistics of test groups 1 and 10-12 liquid fuel

[0093]

[0094] Note: Oil yield = oil mass / plastic mass * 100%; gasoline range yield = gasoline mass / oil mass * 100%; aviation fuel range yield = aviation fuel mass / oil mass * 100%; diesel range yield = diesel mass / oil mass * 100%.

[0095] Experimental conclusion: Based on the data of the above test groups 1, 13 to 15 and Figure 4-5 It was found that when the feedstock to catalyst (15% O-AC) ratio was fixed at 1:1, the pyrolysis temperature (500°C) and nitrogen flow rate (65 mL / min) remained constant, and only the catalyst temperature (450-600°C) was varied, significant differences in oil yield and selectivity for gasoline, aviation kerosene, and diesel were observed. With increasing catalytic temperature, the selectivity for alkanes decreased, while the selectivity for aromatics increased. At high temperatures, the catalyst's ability to cleave C-C and C-H bonds increased, favoring the formation of lower-quality hydrocarbons, thereby increasing selectivity for gasoline and aviation kerosene but decreasing selectivity for diesel. Furthermore, the modified catalyst produced a variety of high-value fuels at different catalytic temperatures. For example, at 450°C, the selectivity for diesel reached 84.89%, at 500°C, the selectivity for aviation fuel reached 93.75%, with alkanes accounting for 78.36% of this; and at 600°C, the selectivity for gasoline reached 92.29%. The modified catalyst not only improved oil quality but also enabled the efficient production of a variety of fuels.

[0096] 2.3 Carbon-based catalyst stability test

[0097] Experimental Group 16: The only difference from Experimental Group 1 is that in step (2), the injection is continuous 1-10 times, 100 mg / time LDPE particles, that is, the carbon-based catalyst is recycled 1-10 times.

[0098] Based on the data of the above experimental group 1 and Figure 6It can be concluded that under the same conditions of pyrolysis temperature (500℃), catalytic temperature (500℃) and nitrogen flow rate (65mL / min), 100 mg of plastic was injected each time, and the injections were continuous for 1-10 times; as the number of injections increased, the selectivity for aviation fuel gradually decreased, but the change was slow; the coal-based activated carbon catalyst modified with 15% hydrogen peroxide had a better pore structure, richer active groups and moderate acidity, showing high selectivity and good catalytic activity and stability, and was able to break long-chain macromolecules in the pyrolysis gas to generate C8~C16 alkanes and a small amount of aromatics, and was not easily deactivated by carbon deposition; the experimental results showed that without any treatment, the catalyst still maintained good catalytic activity after 10 consecutive cycles. Therefore, the catalyst has excellent stability and catalytic performance.

[0099] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.

Claims

1. Application of a carbon-based catalyst in the production of liquid fuel by catalytic pyrolysis of plastics, characterized by: The carbon-based catalyst is prepared by washing coal-based activated carbon with deionized water and setting aside for use, pouring hydrogen peroxide with a mass concentration of 10% to 20% into the coal-based activated carbon to seal and impregnate it, washing the impregnated coal-based activated carbon with deionized water and then drying it to obtain the carbon-based catalyst; wherein the amount of hydrogen peroxide with a mass concentration of 10% to 20% is 30 mL / g; A method for preparing liquid fuel by catalytic pyrolysis of plastic using a carbon-based catalyst comprises the following steps: (1) using an ex situ catalytic pyrolysis method to pyrolyze the plastic, and using an inert gas as a carrier gas to carry the plastic pyrolysis gas into a reactor equipped with the carbon-based catalyst for a catalytic pyrolysis reaction to obtain a gaseous pyrolysis product; The mass ratio of the plastic to the carbon-based catalyst is 1:2 to 2:1; the pyrolysis temperature is 450°C to 600°C, and the pyrolysis reaction time is 25 minutes; the inert gas is nitrogen, and the flow rate of the nitrogen is 55 to 85 mL / min; the catalytic temperature is 450°C to 600°C, and the catalytic reaction time is 25 minutes; (2) The gaseous pyrolysis products are passed through a condensing device containing dichloromethane and methanol, condensed, and collected to obtain liquid fuel; The liquid fuel is aviation fuel C8~C16.

2. The use according to claim 1, characterized in that: The particle size of the coal-based activated carbon is 420-590 μm.

3. The use according to claim 1, characterized in that: The plastic is at least one of low-density polyethylene, high-density polyethylene, polypropylene, polyvinyl chloride, polystyrene, and polyethylene terephthalate.

4. The use according to claim 1, characterized in that: The particle size of the plastic is 1-100 mm.

5. The use according to claim 1, characterized in that: In step (2), the condensation temperature is -15°C to 0°C, and the volume ratio of dichloromethane to methanol is 1:1.

Citation Information

Patent Citations

  • Pyrolysis method of polyolefin waste plastic

    CN112029528A

  • Modified activated carbon preparation method

    RU2240863C1